1
$\begingroup$

How do I evaluate the limit $$ \lim_{x \to 0}\frac{e^{x^2-x} -1 + x - \alpha x^2 + x^4 \log x }{\cosh (2x) -1 + x^4 \sin (1/x^2)}$$

depending on $\alpha, $using Taylor series? I know I consider

$e^t = 1 +t +\frac{t^2}{2} + o(t^2)$

$ \log(1+t) = t - \frac{t^2}{2} + \frac{t^3}{3} + o(t^3)$

$\cosh(t) = 1+ \frac{t^2}{2} + \frac{t^4}{24} + o(t^4)$

$\sin(t) = t - \frac{t^3}{6} + \frac{t^5}{120} + o(t^5)$

and substitute. I know why it is possibile and to justify this method. Though, I am not able to solve this limit... Thanks!

$\endgroup$
1
  • 1
    $\begingroup$ So why don't you show us plugging stuff in. I can already see that the $1's$ cancel due to e-power and cosh(2x) terms. Next, you may be able to cancel common $x$ terms as a result of the constants gone. $\endgroup$ – imranfat Feb 2 '18 at 16:50
1
$\begingroup$

Note that

$$\begin{cases}x^3 \cdot x \sin (1/x^2)\to 0 \implies x^4\sin (1/x^2)=o(x^3)\\\\ x^3 \cdot x\log x\to 0\implies x^4\log x=o(x^3)\\\\ e^{x^2-x} -1 =x^2-x+\frac{(x^2-x)^2}{2}+o(x^2)=-x+\frac32x^2+o(x^2)\\\\ \cosh 2x=1+2x^2+o(x^2)\end{cases}$$

thus

$$\frac{e^{x^2-x} -1 -\alpha x^2 + x^4 \log x }{\cosh (2x) -1 + x^4 \sin (1/x^2)} =\frac{-x+\frac32x^2+o(x^2) - \alpha x^2 + o(x^3) }{1+2x^2+o(x^2) -1 + o(x^3)} =\frac{-x+\left(\frac32-\alpha \right)x^2 +o(x^2) }{2x^2+o(x^2)}=\frac{-\frac1x+\left(\frac32-\alpha \right) +o(1) }{2+o(1)}\to\pm\infty $$

therefore $$\lim_{x \to 0}\frac{e^{x^2-x} -1 - \alpha x^2 + x^4 \log x }{\cosh (2x) -1 + x^4 \sin (1/x^2)}$$

does not exist.

$\endgroup$
2
  • $\begingroup$ Thanks! I forgot the term $+x$ in the numerator, so it's just $-\alpha$. By the way, I can do it solve it on my own now. Just a doubt, when you expand $e^{x^2-x}$, is it not $o(x^4)$? Because if I substitute I get $o((x^2-x)^2) = o(x^4)$. $\endgroup$ – Francesco Gemma Feb 3 '18 at 15:15
  • $\begingroup$ You are welcome! How you can see now, $\alpha$ term is not important here for that I let $\pm$ also if I presumed it was a typo. Note that $o((x^2-x)^2)=o(x^4-2x^3+x^2)=o(x^2)$. If you have doubts on it refer to the definition $o((x^2-x)^2)=(x^2-x)^2\cdot \omega ((x^2-x)^2)$. The key point in this limit is just to recognize, by the definition, that $x^4\log x$ and $x^4 \sin(1/x^2)$ are both $o(x^3)$ otherwise since you can't expand them it should be difficult conclude. $\endgroup$ – user Feb 3 '18 at 15:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.